Applied Interpreting Studies at the core of teaching the instructors: a proposal of solutions - Furmanek, Olgierda (The Journal of Specialised Translation, 2010)
Firstly this paper aims to bring the need to educate student interpreters' instructors to the forefront of research: It advocates a subfield within Interpreting Studies that could be called Applied Interpreting Studies, modelled upon Applied Linguistics, which focuses on trying to resolve language-based problems that people encounter in the real world (Grabe 2002: 9). Secondly it suggest ways to approach the design of teaching interpreting didactics by presenting a pilot program that took place at Wake Forest University in North Carolina, USA in the Fall of 2009. Rather than propose a prescriptive model for teaching teachers of interpreting a spectrum of practicable, modifiable solutions is offered. Following Daniel Gile's statement in the conclusion of his article Teaching Conference Interpreting (Tennent 2005:149), I believe that, as he put it, "It is best to keep one's mind open to a wide range of possibilities, including methods that deviate considerably from the ones advocated most often in the literature."